Financial liberalisation, stock markets and economic development - Singh, Ajit (Nova Economia, 2013)
The paper concentrates on the role of the stock markets in the liberalisation process in DCs in the 1980s and 1990s, and explores, among other things, their effects on the financing of corporate growth. The observed financing patterns will be seen to contradict the predictions of most economic models, and are therefore surprising not just for the M.S, but also for other economists. At the macro-economic level, the paper considers foreign portfolio f1ows, the interactions between the stock and the currency markets, and their implications for the stability of the real economy and its long-term growth.